Effect of Integrated Nutrient Management on Growth and Yield Characteristics of Cauliflower (Brassica oleracea var. botrytis L.) cv. Pant Shubhra under Subtropical Conditions of Uttar Pradesh - Kumar, Vishal; Kushwaha, Jitendra Kumar; Singh, Aman; Chowdhury, Riman Saha (International Journal of Economic Plants, 2024)
A field experiment was conducted during rabi season (September to January) of 2021 and 2022 at the experimental farm of Integral Institute of Agricultural Science and Technology, Integral University, Lucknow, Uttar Pradesh, India. The objective of the experiment is to find out the most efficient combination of different organic and inorganic sources of nutrients to increase the growth, yield characteristics of cauliflower. Total nine numbers of treatments along with the control treatment were assessed in Randomized Block Design with three numbers of replications. In view of, effect of different organic and inorganic sources of nutrients has observed significant variation. The result revealed that the growth parameters like plant height (5.57, 12.47, 19.77 cm), number of leaves (7.97, 9.53, 13.7), length of leaves (17.30, 24.73, 31.73 cm), width of leaves (7.17, 10.20, 15.10 cm), plant spread (285.50, 806.93, 1212.83 cm) at 20, 40 and 60 days respectively, yield parameters like weight of curd (893.73 g), yield of curd plot-1 (13.40 kg), yield of curd ha-1 (25.30 t) were observed higher in 75% N through RDF+25% N through FYM+Azotobacter @ 5 kg ha-1 (T4). INM treatments showed lesser result on growth and yield of cauliflower in T1 (control). The treatment T4 were the most beneficial treatment which may be followed for commercial cauliflower cultivation on large scale. Thus, farmers are suggested to apply 75% N through RDF+25% N through FYM+Azotobacter @ 5 kg ha-1 to increase growth and yield of cauliflower.